2003
DOI: 10.2337/diabetes.52.2.492
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Glycated Insulin in Human Diabetic Plasma and Decreased Biological Activity Assessed by Euglycemic-Hyperinsulinemic Clamp Technique in Humans

Abstract: . Measurement of glycated insulin in plasma of type 2 diabetic subjects by specific RIA gave circulating levels of 10.1 ؎ 2.3 pmol/l, corresponding to ϳ9% total insulin. Biological activity of pure synthetic monoglycated insulin (insulin B-chain Phe 1 -glucitol adduct) was evaluated in seven overnight-fasted healthy nonobese male volunteers using two-step euglycemichyperinsulinemic clamps (2 h at 16.6 g ⅐ kg ؊1 ⅐ min ؊1 , followed by 2 h at 83.0 g ⅐ kg ؊1 ⅐ min ؊1 ; corresponding to 0.4 and 2.0 mU ⅐ kg ؊1 ⅐ mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
76
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 54 publications
(53 reference statements)
5
76
0
1
Order By: Relevance
“…It is also potentially interesting that insulin is normally glycated in vivo and that glycated insulin has reduced biological activity (24,25) . This raises the possibility that inhibition of protein glycation may have benefits in addition to serving as a prophylactic for diabetic complications.…”
Section: Discussionmentioning
confidence: 99%
“…It is also potentially interesting that insulin is normally glycated in vivo and that glycated insulin has reduced biological activity (24,25) . This raises the possibility that inhibition of protein glycation may have benefits in addition to serving as a prophylactic for diabetic complications.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence includes the demonstration of increased concentrations of glycated insulin in the pancreas of various animal models of diabetes [1,8,9] and the time-and concentration-dependent glycation of insulin in both isolated mouse islets or clonal insulin secreting cell lines under hyperglycaemic conditions [1,2]. We have previously shown the impaired biological activity of glycated insulin using in vitro studies with isolated muscle preparations and in vivo studies using animal models or healthy human subjects subjected to hyperinsulinaemic euglycaemic glucose clamps [3,4,5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that glycated insulin has a reduced ability to regulate plasma glucose homeostasis in vivo and to stimulate adipose tissue lipogenesis or glucose uptake and oxidation by isolated diaphragm and abdominal muscle in vitro [3,4,5]. Studies in healthy human volunteers using the hyperinsulinaemic-euglycaemic glucose clamp technique suggest that glycated insulin could contribute to insulin resistance in Type 2 diabetes mellitus [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamic relationship between insulin resistance and b-cell function can be seriously impaired by chronic hyperglycaemia through 'glucotoxicity' (Yki-Jarvinen, 1992) which can exacerbate both fundamental defects, aggregated by environmental factors superimposed on genetic predisposition to insulin resistance and type 2 diabetes. Under conditions of glucotoxicity, insulin is glycated in the pancreatic b-cell and may be released into the circulation in this form (Abdel-Wahab et al 1996;Hunter et al 2003). Glycated proteins including HbA 1c and insulin do not have the same properties as parental molecules; in the case of glycated insulin, this glycated form is likely to contribute to the progressive deterioration of glucose tolerance in diabetes (Hunter et al 2003;Kaiser et al 2003).…”
Section: Genes Environment and The Mechanisms Of Insulin Resistancementioning
confidence: 99%